Butea superba (Roxb.) improves penile erection in diabetic rats - C. Tocharus (2018)
The objective of the present study was to investigate the effect of ethanolic extract of Butea superba (Roxb.) on erectile dysfunction in diabetic rats by the measurement of intracavernous pressure (ICP) and on cavernosal smooth muscle relaxation. Male Sprague-Dawley rats were induced to become diabetic by a single intravenous injection of Streptozotocin (55mgkg -1 body weight). The ethanolic extract at the concentration of 1, 10 and 100mgkg -1 BW was administered orally once a day to diabetic rats in each group for 4weeks. Diabetic rats showed a significant decrease in both ICP and the relaxation of the cavernosal smooth muscle compared with the normal rats. The extract of B. superba significantly increased the ICP with the effective dose of 10mgkg -1 BW (61.00±11.11mmHg versus 39.61±11.01mmHg in the diabetic control group). Moreover, the B. superba-treated group also showed enhanced relaxation of the cavernosal smooth muscle with EC 50 of 1.17mgml -1. These results suggest that the extract of B. superba enhanced penile erection in diabetic rats by increasing the ICP. This might be explained by the increased blood flow as a result of the relaxation of the cavernous smooth muscle. © 2011 Blackwell Verlag GmbH.